PENGEMBANGAN MULTIMEDIA PEMBELAJARAN DALAM MENINGKATKAN EFEKTIVITAS PEMBELAJARAN PADA MATA KULIAH KOMPUTER DAN MEDIA PEMBELAJARAN PRODI PGSD IKIP PGRI MADIUN - Liya Atika Anggrasari (Universitas PGRI Madiun, 2016)
Research and development is intended to produce multimedia learning course on Computer and Media Education for students of primary school teaching as a viable learning medium. The research was conducted with the adaptation of the model development research Borg & Gall. These stages are the preliminary study stage include library research and field study. Product development phase include planning, design learning, producing multimedia and expert validation. Pilot phase trial products include a one-one, small group and large group. Subject trial Prodi PGSD fourth semester student. Data were collected through questionnaires and observations, the results were analyzed by quantitative descriptive analysis. The results showed that: (1) multimedia learning has been generated through five stages of development; (2) the feasibility aspects of learning, content, appearance and technical learning multimedia product is included in both categories with a score of 4.08 in a row; 4.32; 4.00; and 4.07; and (3) learning multimedia product can improve the effectiveness of learning computer courses and learning media. These results make it worth the learning multimedia learning courses as a source of Computer and Media Education for Teachers' Training College students Prodi PGSD PGRI Madiun.